Electrochemically reduced graphene oxide-based screen-printed electrodes for total tetracycline determination by adsorptive transfer stripping differential pulse voltammetry - Lorenzetti, Anabela Silvana (2019)
Disposable electrochemically reduced graphene oxide-based (ERGO) screen-printed electrodes (SPE) were developed for the determination of total tetracyclines as a sample screening approach. To this end, a selective adsorption-detection approach relied on adsorptive transfer stripping differential pulse voltammetry (AdTDPV) was devised, where the high adsorption capacity and the electrochemical properties of ERGO were simultaneously exploited. The approach was very simple, fast (6 min.), highly selective by combining the adsorptive and the electrochemical features of tetracyclines, and it used just 10 μL of the sample. The electrochemical sensor applicability was demonstrated in the analysis of environmental and food samples. The not-fully explored AdTDPV analytical possibilities on disposable nanostructured transducers become a new tool in food and environmental fields; drawing new horizons for “in-situ” analysis.